Wear analysis of ZTA-Mgo ceramic cutting inserts on stainless steel 316L machining - Mohd Ali, Afifah; Ahmad Azhar, Ahmad Zahirani; Ratnam, Mani Maran; Ahmad, Zainal Arifin (Trans Tech Publications, Switzerland, 2015)
The performance of zirconia toughened alumina with addition of MgO additives is investigated. Optimized composition of MgO at 1.1 wt% was used in the composition with alumina/yittria stabilized zirconia (YSZ). The composition was mixed, uniaxially pressed into rhombic 80º cutting inserts with 0.8 mm nose radius and sintered at 1600ºC for 4 h in pressureless condition. For machining analysis, commercial stainless steel 316L with 12 mm diameter were used as workpiece. The workpiece was machined at 625 to 1750 rpm. Tool wear and surface roughness of workpiece were measured. Result shows three types of wear behaviour appear which are flank wear, notch wear and chipping. Flank wear and notch wear increased with the cutting speed but decrease by increasing the feed rate before increased after passing the 0.2mm/rev feed rate. While chipping very much related to the feed rate as the chipping area increased when the feed rate increased. Meanwhile, surface roughness increase with increment of cutting speed and feed rate which match the wear pattern.